2017
DOI: 10.1075/ihll.14.04cas
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 4. The yes-no question contour in Brazilian Portuguese

Abstract: The main goal of this paper is to provide a phonological analysis of neutral yes-no questions in Brazilian Portuguese in seven varieties (Paraíba, Sergipe, Bahia, Minas Gerais, Rio de Janeiro, Santa Catarina and Rio Grande do Sul), most of them along the Atlantic Coast. The analysis followed the autosegmental-metrical framework (Ladd, 2008), and the P-ToBI system for intonational labeling (Frota et al. 2015a). The distribution of the nuclear contour indicates a geographical continuum, where a rising contour is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Finally, a monotonal pitch accent (L*) and a bitonal boundary tone (HL%) are found in the South (Rio Grande do Sul), as another instance of a rising-falling contour shown in Figure 1, bottom panel. These intonational patterns have been extensively studied in previous production research (Castelo and Frota, 2015;Castelo and Frota, 2017;Frota et al, 2015). For BP, some studies have also shown that the pre-nuclear contour has slightly higher F0 values in interrogatives in the Rio de Janeiro (Moraes, 2008) and these values seem to be clearly higher for interrogatives in Northeastern varieties (Lira, 2009).…”
Section: Previous Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, a monotonal pitch accent (L*) and a bitonal boundary tone (HL%) are found in the South (Rio Grande do Sul), as another instance of a rising-falling contour shown in Figure 1, bottom panel. These intonational patterns have been extensively studied in previous production research (Castelo and Frota, 2015;Castelo and Frota, 2017;Frota et al, 2015). For BP, some studies have also shown that the pre-nuclear contour has slightly higher F0 values in interrogatives in the Rio de Janeiro (Moraes, 2008) and these values seem to be clearly higher for interrogatives in Northeastern varieties (Lira, 2009).…”
Section: Previous Studiesmentioning
confidence: 86%
“…Production studies have described a North versus Center-South divide, with rising patterns in the North only, and rising-falling patterns in the Center and South. They have also found an increasingly more frequent use of the rising-falling contour from North to South (Castelo and Frota, 2015;Castelo and Frota, 2017;Frota et al, 2015). These two features were reflected in the perception data.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely studied interrogatives is the information-seeking or 'neutral' yes-no question which corresponds to a request for information without the expectation of a positive or negative answer and is characterised by the absence of focus on any of the words in the question (de Moraes 2008). The description of Brazilian Portuguese intonation is based on data from Castelo and Frota (2017);de Moraes (2008); Rosignoli and Fernandes-Svartman (2016); Silva (2012);, see Table 1. 1 In SEP, neutral yes-no question intonation is characterised by an obligatory final rise, as shown below in (1), for which Frota (2002) proposes the notation H+L* LH%.…”
Section: Yes-no Interrogatives In Portuguesementioning
confidence: 99%
“…Intonation contours of Southern varieties of Brazilian Portuguese are of special interest for this study since they display very different tunes when compared to SEP and Standard German intonation. The contours proposed for the FLBP and SPBP varieties are characterised by a rising tone associated with the nuclear syllable, often followed by a falling tone at the right boundary (Castelo 2016;Castelo and Frota 2017). Although variations in tonal alignment have been observed, the circumflex shape towards the edge of the contour-illustrated for FLBP in (3)-makes it a salient configuration when compared to SEP or German.…”
Section: Yes-no Interrogatives In Portuguesementioning
confidence: 99%
“…Castelo ( 2016) and Castelo and Frota (2017) picture the intonation of BP yes-no questions as a geographic continuum. The authors categorized as 'North' the capitals of Paraíba (PBa), Sergipe (SE), and Bahia (BA), as 'Center' the capitals of Rio de Janeiro (RJ), and Minas Gerais (MG), and as 'South' the capitals of Santa Catarina (SC), and Rio Grande do Sul (RS).…”
Section: Neutral Yes-no Questions Of European Brazilian and African V...mentioning
confidence: 99%